Sport and physical activities: actual Ukraine’s strategic narrative (in terms of encyclopedias) - Mykola Zhelezniak; Oleksandr Ishchenko; Zhanneta Kozina; Ratko Pavlović (Здоров’я, спорт, реабілітація)
Background and purpose